The Adventures of a Girl Called Bicycle - Uss, Christina (New York : Margaret Ferguson Books, Holiday House, 2018)
Left at the Mostly Silent Monastery as a toddler and home-schooled by a retired nun, twelve-year-old Bicycle rides cross-country to meet a famous cyclist who she hopes will be her first friend.
Keywords: Bicycles -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Friendship -- Juvenile fiction; Nuns -- Juvenile fiction; Monasteries -- Juvenile fiction; Foundlings -- Juvenile fiction; Bicycles and bicycling -- Fiction; Voyages and travels -- Fiction; Friendship -- Fiction; Nuns -- Fiction; Monasteries -- Fiction; Foundlings -- Fiction